Dark Matter Genesis - Jeremy Mould (The Astrophysical Journal)
Recent discoveries of primordial black hole (PBH) candidates by means of high-cadence microlensing open the way to a physical understanding of the formation of dark matter as a chapter in the thermal history of the Universe. Two complementary sites of PBH formation are considered, inflation and the early Universe at TeV to MeV energies. In the latter case the Friedmann equation, together with mass measurements, reveal the threshold energy, the mass spectrum, and the likely end point of this epoch. Some of the many recent exoplanet detections may conceivably have been detections of PBHs. When the Universe cools to MeV temperatures, larger-mass PBHs would form similarly, reaching the supermassive regime. The discovery of numerous supermassive black holes at high redshift with JWST fulfils this expectation. We corroborate the idea that Planck mass relics could be an important component of dark matter, and find that these are formed by PBHs with initial mass less than approximately 6 × 10 ^−16 M _⊙ and cosmic temperature above 10 ^9 GeV. Although in some mass ranges PBHs can only make up a modest fraction of Ω _m , it is possible that all astrophysical dark matter, as distinct from axions and weakly interacting massive particles, is of PBH origin.